2008
DOI: 10.1016/j.abb.2008.01.027
|View full text |Cite
|
Sign up to set email alerts
|

The growing VAO flavoprotein family

Abstract: The VAO flavoprotein family is a rapidly growing family of oxidoreductases that favor the covalent binding of the FAD cofactor. In this review we report on the catalytic properties of some newly discovered VAO family members and their mode of flavin binding. Covalent binding of the flavin is a self-catalytic post-translational modification primarily taking place in oxidases. Covalent flavinylation increases the redox potential of the cofactor and thus its oxidation power. Recent findings have revealed that som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 74 publications
(61 reference statements)
1
85
0
10
Order By: Relevance
“…AAO activity in B. adusta (Romero et al 2010), whose sequence corresponds to BJEAD_171002 from the JGI genome, has been characterized largely showing higher activity on p-hydroxy and chlorinated benzyl alcohols than Pleurotus AAO (Romero et al 2009). p-Hydroxybenzyl alcohols are the typical substrates of vanillyl alcohol oxidase, a flavoenzyme from a different superfamily (Leferink et al 2008), but they are not efficiently oxidized by Pleurotus AAO, whose best substrates are p-methoxylated benzyl alcohols (Guillén et al 1992, Ferreira et al 2005. Therefore the best characterized Polyporales AAO shows catalytic properties intermediate between Agaricales AAO and vanillylalcohol oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…AAO activity in B. adusta (Romero et al 2010), whose sequence corresponds to BJEAD_171002 from the JGI genome, has been characterized largely showing higher activity on p-hydroxy and chlorinated benzyl alcohols than Pleurotus AAO (Romero et al 2009). p-Hydroxybenzyl alcohols are the typical substrates of vanillyl alcohol oxidase, a flavoenzyme from a different superfamily (Leferink et al 2008), but they are not efficiently oxidized by Pleurotus AAO, whose best substrates are p-methoxylated benzyl alcohols (Guillén et al 1992, Ferreira et al 2005. Therefore the best characterized Polyporales AAO shows catalytic properties intermediate between Agaricales AAO and vanillylalcohol oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…BBLs belong to an oxidoreductase subfamily that includes BBE (Fig. 1) within a larger vanillyl-alcohol oxidase flavoprotein superfamily (Leferink et al, 2008). The three-dimensional x-ray crystal structures of BBE, glucooligosaccharide oxidase, 6-hydroxy-D-nicotine oxidase, and aclacinomycin oxidoreductase showed that the flavoproteins of the BBE subfamily comprise two domains: a conserved FAD-binding domain and an a/b-domain with a seven-stranded, antiparallel b-sheet forming the less-conserved substrate-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…Reoxidation of the reduced flavin coenzyme can take place via several processes, including the reaction with oxygen, as in the case of flavin oxidases. The flavin cofactors (generally, flavin mononucleotide [FMN] or flavin adenine dinucleotide [FAD]) often are tightly bound to these enzymes, and in selected examples, the coenzyme is covalently attached to the protein (11). Sequence comparisons of YgaF reveal this 422-amino-acid E. coli protein to be homologous to human mitochondrial L-2-hydroxyglutarate dehydrogenase (41% identity over 398 residues) (28), Helicobacter pylori malate:quinone oxidoreductase (24% identity over 421 residues) (33), Bacillus sp.…”
mentioning
confidence: 99%